Готовність педагога до роботи в умовах інклюзивної освіти ЗНЗ - Гудзь, Катерина (My University, 2018)
У статті розглядається проблема готовності майбутніх вчителів початкової ланки освіти до професійної діяльності в умовах інклюзії. Згідно відомостей МОН України, наведено статистичні дані загальної кількості інклюзивних класів, наголошено на проблемі підготовки педагогічних кадрів до роботи в інклюзивних класах. Охарактеризовано поняття «готовність», «професійна готовність», «готовність учителів початкових класів до роботи в умовах інклюзивної освіти». З метою порівняння практичної діяльності фахівців,що уже мають досвід роботи з учнями із особливими потребами та теоретичних знань студентів-майбутніх педагогів після вивчення курсу «Основи інклюзивної освіти» було проведено анкетування, проаналізовано його результати та перспективи подальшого дослідження. The article examines the problem of the future teacher’s readiness of junior pupils to professional activity in the conditions of inclusion. According to the information of the Ministry of Education and Science of Ukraine there are statistics of the total number of inclusive classes in the article. Also, the author emphasized the problem of training pedagogical staff for work in inclusive classes. Such notions as “readiness”, “professional readiness”, “readiness of primary school teachers to work in conditions of inclusive education” was characterized in the article. The author was conducted a questionnaire in order to compare the practical work of specialists (who already have experience with pupils with special needs) and theoretical knowledge of students (future specialists who studied the course “Fundamentals of inclusive education”).Its results and prospects for further research were analyzed. It should be noted about the remoteness of the practical work of a well trained specialist with the theoretical knowledge of the students – future pedagogue. In our opinion, higher education institutions need to cooperate more closely with schools, hold joint events (round tables, trainings, seminars, meetings with leading specialists, open lessons, etc.), involve students in getting acquainted with inclusive classes as early as it possible.
Keywords: готовність; професійна готовність; вчитель; інклюзивна освіта; інклюзивні класи; діти з особливими потребами; студенти; readiness; professional readiness; teacher; inclusive education; inclusive classes; children with special needs; students